Adolescent Alcohol Use Predicts Cannabis Use over A Three Year Follow-Up Period. Issue 1 (December 2022) - Linakis, James G.; Thomas, Sarah A.; Bromberg, Julie R.; Casper, T. Charles; Chun, Thomas H.; Mello, Michael J.; Richards, Rachel; Ahmad, Fahd; Bajaj, Lalit; Brown, Kathleen M.; Chernick, Lauren S.; Cohen, Daniel M.; et al.
Background : Alcohol and cannabis use frequently co-occur, which can result in problems from social and academic impairment to dependence (i.e., alcohol use disorder [AUD] and/or cannabis use disorder [CUD]). The Emergency Department (ED) is an excellent site to identify adolescents with alcohol misuse, conduct a brief intervention, and refer to treatment; however, given time constraints, alcohol use may be the only substance assessed due to its common role in unintentional injury. The current study, a secondary data analysis, assessed the relationship between adolescent alcohol and cannabis use by examining the National Institute of Alcohol Abuse and Alcoholism (NIAAA) two question screen's (2QS) ability to predict future CUD at one, two, and three years post-ED visit. Methods: At baseline, data was collected via tablet self-report surveys from medically and behaviorally stable adolescents 12–17 years old ( n = 1, 689) treated in 16 pediatric EDs for non-life-threatening injury, illness, or mental health condition. Follow-up surveys were completed via telephone or web-based survey. Logistic regression compared CUD diagnosis odds at one, two, or three-year follow-up between levels constituting a single-level change in baseline risk categorization on the NIAAA 2QS (nondrinker versus low-risk, low- versus moderate-risk, moderate- versus high-risk). Receiver operating characteristic curve methods examined the predictive ability of the baseline NIAAA 2QS cut points for CUD at one, two, or three-year follow-up. Results: Adolescents with low alcohol risk had significantly higher rates of CUD versus nondrinkers (OR range: 1.94–2.76, p < .0001). For low and moderate alcohol risk, there was no difference in CUD rates (OR range: 1.00–1.08). CUD rates were higher in adolescents with high alcohol risk versus moderate risk (OR range: 2.39–4.81, p < .05). Conclusions: Even low levels of baseline alcohol use are associated with risk for a later CUD. The NIAAA 2QS is an appropriate assessment measure to gauge risk for future cannabis use.